Eye tracking technology to audit google analytics: Analysing digital consumer shopping journey in fashion m-retail. (August 2021) - Tupikovskaja-Omovie, Zofija; Tyler, David
Highlights: Shopping journeys developed based on eye tracking and Google Analytics data compared. Google Analytics track only half of digital users' activities on retailer's website. Eye tracking documents a full interaction with all elements on fashion retailer's website. Google Analytics provide a limited account about User Experience. Eye tracking has the potential to audit Google Analytics database to improve marketing decision-making. Abstract: Rapid changes in digital consumer behaviour, influenced by exponential adoption of smartphones, require timely and sophisticated responses from retailers to these consumer needs. With a growing amount of big data available, fashion retailers need to innovate and develop more sophisticated analytics for new consumer behaviours such as m-commerce. This research has considered how Google Analytics data can be applied to develop customer journey maps to understand digital consumer behaviour. A multi-method research design was used, incorporating an innovative mobile eye tracking technology and mobile fashion consumer data from Google Analytics. Digital customers' shopping journeys on the fashion retailer's website were mapped using data sourced from eye tracking and Google Analytics, gathered in parallel. The comparison of these shopping journeys allowed a critical evaluation of the precision and usefulness of the Google Analytics database. Google Analytics tracked only half of the digital users' activities, whereas eye tracking data documented digital consumers' interaction with all elements of the fashion retailer's website. The conclusion reached is that eye tracking can be used to audit the Google Analytics database for potential gaps in data and also to inform and improve marketing decision-making.